Impacts of Risk Perception, Disaster Knowledge, and Emotional Attachment on Tourists’ Behavioral Intentions in Qinling Mountain, China - Hao, Junqing; Tang, Han; Hao, Jiawei; Ma, Yanting; Jiang, Xinxiang (Frontiers in Earth Science, 2022)
With natural disasters occurring more frequently around the world, their impact on tourism is becoming a serious problem. The existing literature in the field of tourism disaster management focuses mostly on disaster impact analysis, risk assessment, and post-disaster recovery, while the impact of disaster on tourism and tourists is still a new topic. It is necessary to investigate the correlation between the natural disasters and the tourists’ behavior. Taking the famous tourism destination, Qinling Mountain, located in the middle of China, as an example where frequent mountain disasters happened, we investigated 542 youth group tourists using a questionnaire survey and analyzed the influence of risk perception, disaster knowledge, and emotional attachment on tourists’ travel behavioral intentions. The results showed that 1) risk perception has a negative effect on tourists’ behavioral intentions; 2) disaster knowledge and tourism emotional attachment have a positive effect on tourists’ behavioral intention; and 3) the moderation role of gender is not significant, while the moderation role of education level is significant. Therefore, this analysis is of great importance for research dealing with the theory of tourism disaster and the management practice of disaster-prone tourism destinations.